ANGLICHAN TILINEN ÓZLESTIRILGEN SÓZLERDIŃ NÓKIS KÓSHELERINDE QOLLANÍLIWÍ - Koshanov, К.М. (SCIENCE and SOCIETY, 2023)
This article deals with the borrowings that taken from the English language which are used in the streets of Nukus.